Consumer theory - Green, H. A. John. (London : Macmillan, 1976)
The book is on microeconomic theory in which accounts of theories by other economist is included.
Includes bibliographies and index.
gp. 24/01/2019
Loans
Keywords: Consumption (Economics); Consumers